A tRNA-mimic Strategy to Explore the Role of G34 of tRNAGly in Translation and Codon Frameshifting - Aurélie Janvier (International Journal of Molecular Sciences, 2019)
Decoding of the 61 sense codons of the genetic code requires a variable number of tRNAs that establish codon-anticodon interactions. Thanks to the wobble base pairing at the third codon position, less than 61 different tRNA isoacceptors are needed to decode the whole set of codons. On the tRNA, a subtle distribution of nucleoside modifications shapes the anticodon loop structure and participates to accurate decoding and reading frame maintenance. Interestingly, although the 61 anticodons should exist in tRNAs, a strict absence of some tRNAs decoders is found in several codon families. For instance, in Eukaryotes, G34-containing tRNAs translating 3-, 4- and 6-codon boxes are absent. This includes tRNA specific for Ala, Arg, Ile, Leu, Pro, Ser, Thr, and Val. tRNAGly is the only exception for which in the three kingdoms, a G34-containing tRNA exists to decode C3 and U3-ending codons. To understand why G34-tRNAGly exists, we analysed at the genome wide level the codon distribution in codon +1 relative to the four GGN Gly codons. When considering codon GGU, a bias was found towards an unusual high usage of codons starting with a G whatever the amino acid at +1 codon. It is expected that GGU codons are decoded by G34-containing tRNAGly, decoding also GGC codons. Translation studies revealed that the presence of a G at the first position of the downstream codon reduces the +1 frameshift by stabilizing the G34•U3 wobble interaction. This result partially explains why G34-containing tRNAGly exists in Eukaryotes whereas all the other G34-containing tRNAs for multiple codon boxes are absent.